Case Report: Clinical delineation of CACNA1D mutation: New cases and literature review - Alzahrani, Alshaimaa; Alshalan, Maha; Alfurayh, Mohammed; Bin Akrish, Abdulaziz; Alsubeeh, Najlaa A.; Al Mutairi, Fuad (Frontiers in Neurology, 2023)
Background: We delineate the spectrum of clinical phenotypes and the symptoms associated with a syndrome caused by an inherited CANCA1D missense mutation in a family with a history of neuropsychiatric disorders. We also present a previously reported variant of CACNA1D. Furthermore, we examine the aberrant gating properties of Cav1.3 Ca2+ channels to provide more insight into the therapeutic potential for these patients. Case presentation: We report the case of a 9-year-old female, diagnosed with autism spectrum disorder, severe intellectual disability, hyperactivity, and aggressive impulsive behaviors. The father, who was 65 years old at his death, had an intellectual disability and developed a major depressive disorder with catatonic features and nihilistic delusion, followed by rapidly progressive dementia. He died after experiencing prolonged seizures followed by post-cardiac arrest. The patient’s sister is a 30-year-old female, known to have a severe intellectual disability with aggressive behaviors and sleep disorders. The sister has been diagnosed with bipolar disorder and psychosis. Through whole exome sequencing, a heterozygous missense likely pathogenic variant was identified in the CACNA1D gene (NM_000720.3) c.2015C>T (p.Ser672Leu). These findings are consistent with the genetic diagnosis of autosomal dominant primary aldosteronism, seizures, and neurological abnormalities. This variant was found in the heterozygous status of the patient, her father, and her affected sister. Conclusions: This case report will help to determine the key clinical features of this syndrome, which exhibits variable clinical presentations.